THEORETICAL ANALYSIS OF PRODUCTIVITY OF THE AGRICULTURAL SECTOR FROM THE VIEW OF MACROECONOMIC TRANSFORMATION - Obradović, Saša (Economics of Agriculture, 2010)
The aim of this paper is to provide the methodological basis for the possible direction of analysis of the correlation of output and productivity in agriculture. The basic intention of the author is to explain and show the concept on the basis of general theoretical statements present in macro-economic science, that can be used in the analysis of the agricultural sector. The concept of modeling changes in productivity based on the modernization and transformation of agriculture in accordance with the degree of economic development оf the observed country. The results that come up in the paper provide a basis for interpreting the changes that are occurring in the agricultural sector with the introduction of technological innovations and increasing the funds of various types of capital.